Poverty in Russia: A Bird's-Eye View of Trends and Dynamics in the Past Quarter of Century - Kseniya Abanokova; Hai-Anh H. Dang (Global Labor Organization (GLO), 2021)
Hardly any recent study exists that broadly reviews poverty trends over time for Russia. Analyzing the Russian Longitudinal Monitoring Surveys between 1994 and 2019, we offer an updated review of poverty trends and dynamics for the country over the past quarter of century. We find that poverty has been steadily decreasing, with most of the poor having a transient rather than a chronic nature. The bottom 20 percent of the income distribution averages an annual growth rate of 5 percent, which compares favorably with that of 3.3 percent for the whole population. Income growth, particularly the shares that are attributed to labor incomes and public transfers, have important roles in reducing poverty. Our findings are relevant to poverty and social protection policies.
Keywords: C15; D31; I31; O10; O57; 330; poverty; poverty dynamics; income growth; income mobility; RLMS; Russia